Focal adhesion kinase is involved in the migration of human osteosarcoma cells - FENG, SITAN (Oncol Lett, 2015)
The aim of the present study was to analyze the expression of focal adhesion kinase (FAK) in osteosarcoma (OS) cell lines with different migration abilities in order to determine the role of FAK in migration. A number of different 143B subclone cell lines (A1, A2, A3, A4 and A5) were obtained by a limiting dilution method, and the expression of FAK was detected using western blot analysis. The role of FAK in the migration of OS cells was investigated using small interfering RNA (siRNA), and the ratio of the number of lamellipodia was compared by immunofluorescence staining. The A2 and A3 OS 143B subclone cell lines demonstrated a stronger migration ability and exhibited higher FAK expression compared with the A1 cell line (P<0.05). Following transfection with FAK-siRNA, the migration ability of the A3 cells was significantly decreased (P<0.05), and the ratio of the number of lamellipodia formed was reduced from 35 to 11% (P<0.05). In conclusion, the level of FAK expression was higher in the cell lines with a stronger migration ability. FAK affects the migration ability of OS cells by suppressing the formation of lamellipodia.